1997
DOI: 10.1074/jbc.272.39.24684
|View full text |Cite
|
Sign up to set email alerts
|

Role of Janus Kinase/Signal Transducer and Activator of Transcription and Mitogen-activated Protein Kinase Cascades in Angiotensin II- and Platelet-derived Growth Factor-induced Vascular Smooth Muscle Cell Proliferation

Abstract: In vascular smooth muscle cells, the induction of early growth response genes involves the Janus kinase (JAK)/ signal transducer and activators of transcription (STAT) and the Ras/Raf-1/mitogen-activated protein kinase cascades. In the present study, we found that electroporation of antibodies against MEK1 or ERK1 abolished vascular smooth muscle cell proliferation in response to either platelet-derived growth factor or angiotensin II. However, anti-STAT1 or -STAT3 antibody electroporation abolished proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 24 publications
3
170
1
1
Order By: Relevance
“…G proteins have been also implicated in the tyrosinephosphorylation and subsequent activation of the STAT-family of transcription factors (Bhat et al, 1994;Marrero et al, 1997). It has been observed that the stimulation of the AT 1 -Angiotensin II receptor that primarily couples through G q results in the phosphorylation of STAT-1 and STAT-3 through a JAK2-mediated mechanism.…”
Section: G Protein Interactions With Other Signaling Pathwaysmentioning
confidence: 99%
“…G proteins have been also implicated in the tyrosinephosphorylation and subsequent activation of the STAT-family of transcription factors (Bhat et al, 1994;Marrero et al, 1997). It has been observed that the stimulation of the AT 1 -Angiotensin II receptor that primarily couples through G q results in the phosphorylation of STAT-1 and STAT-3 through a JAK2-mediated mechanism.…”
Section: G Protein Interactions With Other Signaling Pathwaysmentioning
confidence: 99%
“…49 Significantly, recent research indicates that angiotensin II also mediates proliferative effects through the Jak/STAT signalling pathway, which leads to the transcription activation of early growthresponse genes. 50,51 While much less is known about the functional properties of the AT 2 receptor, it would appear that it mediates the effects of angiotensin II on growth control and cell differentiation, as well as neuronal differentiation and apoptosis [52][53][54][55][56] (Table 2). The AT 2 -receptor-mediated effects down-modulate the actions by the AT 1 receptor, resulting in decreased cellular proliferation, modulation of AT 1 -mediated vasopressin release in certain experimental conditions and a decreased vasoconstrictor response.…”
Section: Characterisation Of the Angiotensin II Receptorsmentioning
confidence: 99%
“…64 Also, antibodies against STAT proteins in vascular smooth muscle cells inhibit the Ang II mediated proliferative response. 65 A physical association between Jak2 kinase and a part of the intracellular carboxy tail of the AT 1 receptor has been shown as well. 66 Very recently it has been shown that Ang II mediates the Jak/STAT pathway under pathological conditions as well.…”
Section: At 1 Receptor and Signal Transductionmentioning
confidence: 91%